Description of Parenting Patterns with Nutritional Status of Toddlers Aged 12-60 Months in RW 02 Simokerto Urban Village Surabaya City - Setyobudihono, Sudjatmiko; Aprianti, Rita; Apriliyani, Tyas Sekar (Jurnal EduHealth, 2025)
The quality of future human resources is influenced by current child health problems, which are an important national issue. The first five years are a crucial period in a child's growth and development that determines their physical, psychological and intelligence. Based on SSGI 2022 data, the prevalence of stunting in Indonesia reached 21.6%, wasting 7.7%, and underweight 17.1% (Kemenkes RI, 2022). This study aims to determine the description of parenting patterns with the nutritional status of toddlers aged 12-60 months in RW 02 Simokerto Village, Surabaya. This study used a quantitative approach with an analytic observational design, involving 33 respondents selected through total sampling. Data analysis used descriptive univariate and bivariate tests. The results showed that authoritative parenting was applied to 28 mothers, where 23 children had good nutrition and 5 children were malnourished. Permissive parenting was applied to 2 children with good nutrition, while authoritarian parenting was applied to 3 children, with 2 children well-nourished and 1 child undernourished. This study concludes that parenting patterns affect the nutritional status of children under five, with authoritative patterns being the most dominant and associated with good nutrition.